Relationship Levels of Knowledge About Hepatitis B Disease with HBsAG Checking Measures on Pregnant Women at Puskesmas Dolok Masihul, Serdang Bedagai Regency - Desideria Yosepha Ginting (Universitas Aisyah Pringsewu, 2020)
The purpose of this study was to determine the relationship between the level of knowledge about hepatitis B disease and HBsAg examination in pregnant women at the Dolok Masihul Public Health Center, Serdang Bedagai Regency in 2020. This research method was a quantitative study with a descriptive correlation research design with a cross-sectional approach. at the Dolok Masihul Health Center, Dolok Masihul District, Serdang Bedagai Regency. starting from January to July 2020. The results of this study are 1 The level of knowledge of pregnant women about hepatitis B at the Dolok Masihul Public Health Center, Serdang Bedagai Regency in 2020 is mostly less (46.8%). 2 The majority of HBsAg examinations for pregnant women at the Dolok Masihul Public Health Center, Serdang Bedagai Regency in 2020 were not carrying out HBsAg examination (72.3%). 3 There is a relationship between the level of knowledge about hepatitis B and the action of HBsAg examination in pregnant women at the Dolok Masihul Public Health Center, Serdang Bedagai Regency in 2020 with a p-value = 0.000.